(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Mushrooms have long been used for medicinal and food purposes. Pleurotus sajor- caju isedible mushroom species. In present study, Pleurotus sajor -caju was cultivated on wheat straw andduring its growth various doses of Indole 3 acetic acid (IAA) a plant hormone at 10ppm, 50ppm and100ppm were sprayed in mushroom substrate. Thereafter its effect on the growth and yield of all threeflushes were recorded. Results showed that IAA was able to induce stimulation in growth and ultimatelyincrease in yield is also recorded. Various doses of IAA resulted in increased biomass production from14 to 30 with reference to control. This study suggest that exposure of the hormone to substratecan be important tool to increase the production of mushroom and thereby increase nutrition demandcan be fulfilled.